Analisis Dampak Program Keluarga Harapan (PKH) Pada Masyarakat Kecamatan Teras Terunjam Kabupaten Mukomuko - Darson, Darson; Alexsander, Alexsander; Sakti, Budiman; Harmiati, Harmiati (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2025)
This study aims to analyze the impact of the Family Hope Program (PKH) on the community of Teras Terunjam Subdistrict, Mukomuko Regency, in terms of policy and budgeting aspects. It also aims to examine the factors that influence the implementation of the Family Hope Program (PKH) in the community of Teras Terunjam Subdistrict, Mukomuko Regency. To address these issues, the researcher employed a qualitative research method. The results of the study show that the evaluation of the context of service delivery for the Family Hope Program (PKH) in the community of Teras Terunjam Subdistrict, Mukomuko Regency, has been generally good. Based on findings from informants, the services provided—from document submission to home surveys—have been carried out according to procedures. Observations and interviews also indicate that the service delivery of the Family Hope Program (PKH) in this area is fairly good, although there are still some instances where certain services provide special treatment for relatives in accessing direct cash assistance.